Physical Fitness Results of Soldiers Of Different Age Groups in the Land Force of the Lithuanian Professional Armed Forces in 2010–2011 (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Since 2009 Lithuanian Armed Forces have been formed from soldiers in professional service. Research on military physical fitness in the Lithuanian Armed Forces is scarce. This research aims  at  verifying  the  hypothesis  that  physical  fitness  indices  of  soldiers  in  the  Land  Force  of  the  professional Lithuanian Armed Forces match the established physical fitness normative requirements.Research aim was to study peculiarities of changes in physical fitness results of soldiers of different age groups in the Land Force of the Lithuanian Professional Armed Forces in the period of two years. Research  methods:  literature  review,  physical  fitness  testing,  statistical  analysis  of  physical  fitness  indices. Results in each physical fitness exercise were evaluated in points according to physical fitness normative scales. The sum of points for all exercises was the final physical fitness evaluation result. Research results. In the period of half a year, from spring to autumn and from autumn to spring, physical fitness of soldiers in all age groups changed only slightly (p > 0.05). During the period of one year, from testing in spring till testing in spring of the following year, physical fitness indices improved (p < 0.05). Even 2–4% of soldiers failed physical fitness normative tests. Discussion and conclusions. Physical fitness indices of different exercise for soldiers in the Land Force of the professional Lithuanian Armed Forces were higher than the established minimal normative requirements. The highest physical fitness indices were achieved in the age groups of 18–21, 22–26, 27–31 and 30–36 years, however, the differences between the age groups were insignificant. In perspective, while developing military physical fitness control system, the evaluation of physical fitness should be differentiated according to the normative scale which includes such evaluations as “excellent”, “good”,  “fair”.Keywords: Land Force, physical fitness, testing, physical fitness test, age group, points.